Temporal and Spatial Expression Patterns of miR-302 and miR-367 During Early Embryonic Chick Development - Jeong, Hoe-Su (Int J Stem Cells, 2014)
The microRNAs (miRNAs) are small, non-coding RNAs that modulate protein expression by interfering with target mRNA translation or stability. miRNAs play crucial roles in various functions such as cellular, developmental, and physiological processes. The spatial expression patterns of miRNAs are very essential for identifying their functions. The expressions of miR-302 and miR-367 are critical in maintaining stemness of pluripotent stem cells, including embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) but their functions in early development are not fully elucidated. So, we used Locked Nucleic Acid (LNA) probes to perform in situ hybridization and confirmed the temporal and spatial distribution patterns during early chick development. As a result, we found that miR-302 and miR-367 were expressed in various tissues such as primitive steak, neural ectoderm, neural plate, neural fold, neural tube, notochord, and oral cavity. Specially, we confirmed that miR-302 and miR-367 were strongly expressed in neural folds in HH8 to HH10. miR-302 was expressed on dorsal part of the neural tube but miR-367 was expressed on lateral and ventral parts of the neural tube. And also we performed quantitative stem-loop real-time PCR to analyze global expression level of miR-302 and miR-367. miR-302 and miR-367 expression was sustained before Hamburger and Hamilton stage (HH) 14. Thus, the temporal and spatial expression patterns of miR-302 and miR-367 may provide us information of the role of these miRNAs on tissue formation during early chick development.